Improving the Performance of Competitive Activity of Volleyball Players based on the Correction of Techniques - N. Konopleva, Anna; V. Kerzhentseva, Anna; A. Kozhemov, Aslan; Z. Bazhev, Arsen; V. Kardanova, Elena; V. Dadov, Aslan; S. Zolotareva, Irina (International Journal of Psychosocial Rehabilitation, 2020)
Object: Improving the serve effectiveness in volleyball using urgent information.Methods: theoretical analysis, review of sources, and scientific data by studying the scientific, methodical, and program-normative literature on the problem; pedagogical observation; testing the technical preparedness level of volleyball players (control exercise method); biomechanical characteristics registration; formative experiment; mathematical processing of the results.Findings: The paper analyzes the biomechanical parameters when performing the floating and power serve in the unsupported position. The interrelation between the indicators and the effectiveness of implementing this technique in competitive activity is shown. Based on the data of the optoelectronic biomechanical complex, the main errors in the technique made by the experiment participants are revealed, and the author’s method is presented, which aims at correcting the technique of power and floating serve in the unsupported position (in the group of volleyball players studied).Conclusions: The possibilities of using urgent information in training athletes at various levels are shown. The work substantiates the expediency of using optoelectronic biomechanical complexes for flat and three-dimensional methods of locomotion research for the correction of gaming techniques.